% vim: tw=50 % 18/10/2022 10AM \subsubsection*{Communicating classes} \begin{flashcard} \begin{definition*}[Communicating classes] Let $X$ be a Markov Chain with matrix $P$ on $I$. Let $x, y \in I$. We say $x \to y$ ($x$ leads to $y$) if \[ \cloze{\PP_x(X_m = y \text{ for some } m \ge 0) > 0 .} \] We say that $x$ and $y$ communicate and $x \comm y$ if both $x \to y$ and $y \to x$. \end{definition*} \end{flashcard} \begin{theorem*} The following are equivalent: \begin{enumerate}[(1)] \item $x \to y$ \item $\exists$ a sequence $x = x_0, x_1, \dots, x_k = y$ such that \[ P(x_0, x_1) \cdots P(x_{k - 1}, x_k) > 0 \] \item $\exists n \ge 0$ such that $p_{xy}(n) > 0$ (recall that $p_{xy}(n)$ is the $(x, y)$ element of $P^n$, and is also equal to $\PP_x(X_n = y)$) \end{enumerate} \end{theorem*} \begin{proof} First we prove (1) $\iff$ (3). We have: \[ \{X_n = y \text{ for some $n \ge 0$}\} = \bigcup_{n \ge 0} \{X_n = y\} \] If $x \to y$, then $\exists n \ge 0$ such that $\PP_x(X_n = y) > 0$. From the definition of $\to$, we immediately have (3) $\implies$ (1). \myskip Now we prove (2) $\iff$ (3): \[ \PP_x(X_n = y) = \sum_{x_1, \dots, x_{n - 1}} p(x, x_1) \cdots p(x_{n - 1}, y) \] so (2) $\iff$ (3). \end{proof} \begin{corollary*} $\comm$ defines an equivalence relation on $I$. \end{corollary*} \begin{proof} $x \comm x$, because $p_{xx}(0) = 1$. Transitivity: suppose $X \comm y$ and $y \comm z$. Then from (2), $x \comm z$. \end{proof} \begin{definition*} The equivalence classes induced by $\comm$ on $I$ are called communicating classes. We say that a class $C$ is \emph{closed} if whenever $x \in C$ and $x \to y$, then $y \in C$. \end{definition*} \begin{hiddenflashcard} \begin{definition*}[Closed communicating class] We say that a communicating class $C$ is \emph{closed} \cloze{whenever $x \in C$ and $x \to y$, then $y \in C$.} \end{definition*} \end{hiddenflashcard} \begin{flashcard} \begin{definition*} A matrix $P$ (transition) is called \emph{irreducible} if \cloze{it has a single communicating class.}\fcscrap{ In other words, $x \comm y$ for all $x, y \in I$.} \end{definition*} \end{flashcard} \begin{definition*} A state $x$ is called \emph{absorbing} if $\{x\}$ is a closed class. Equivalently if the Markov chain started from $x$ then it stays at $x$ forever. \end{definition*} \begin{definition*} $A \subseteq U$. $\tau_A : \Omega \to \NN \cup \{\infty\}$ \[ \tau_A = \inf\{n \ge 0 : X_n(\omega) \in A\} \] \end{definition*} \noindent Convention: $\inf(\emptyset) = \infty$. $\tau_A$ is the first hitting time of $A$. \myskip Denote $h_i^A = \PP_i(\tau_A < \infty)$, $i \in I$. \\ $h^A : I \to [0, 1]$, ($h_i^A : i \in I$) is vector of hitting probability. \myskip Also define $k^A : I \to \RR_+ \cup \{\infty\}$, the mean hitting time. So \[ k_i^A = \EE_i[\tau_A] = \sum_{n = 1}^\infty n \PP_i(\tau_A = n) + \ub{\infty \cdot \PP_i(\tau_A = \infty)}_{0 \cdot \infty = 0} \] \begin{center} \includegraphics[width=0.6\linewidth] {images/f3726f2a4ec711ed.png} \end{center} $\PP_2(\tau_4 < \infty) = h_2^{\{4\}}$. $\tau_4 = \tau_{\{4\}}$. \[ h_2 = \half h_3 + \half h_1 \] \[ h_3 = \half + \half h_2 \] \[ \implies h_2 = \frac{1}{3} \] ($h_1 = 0$, $h_4 = 1$) $k_2^{\{1, 4\}} = \EE_2[\tau_{\{1, 4\}}]$ \[ k_2 = 1 + \half \cdot 0 + \half k_3 \] \[ k_3 = 1 + \half \cdot 0 + \half k_2 \] \[ \implies k_2 = 2 \] $k_1 = k_4 = 0$. \begin{flashcard} \begin{theorem*} Let $A \subseteq I$. The vector $(h_i^A : i \in I)$ is \cloze{a solution to the linear system} \[ \cloze{h_i^A = \begin{cases} 1 & \text{if $i \in A$} \\ \sum_j P(i, j) h_j^A & i \not\in A \end{cases}} \] \cloze{The vector $(h_i^A)$ is the minimal non-negative solution to this system.} \\ \fcscrap{A solution $(h_i^A)$ is minimal if for any other non-negative solution $(X_i)$, we have that $h_i^A \le X_i ~ \forall i$.} \end{theorem*} \end{flashcard} \begin{proof} Clearly, if $i \in A$, then $h_I^A = 1$. Assume $i \not\in A$. \[ h_i^A = \PP_i(\tau_A < \infty) \] \[ \{\tau_A < \infty\} = \bigcup_{n = 0}^\infty \{\tau_A = n\} = \bigcup_{n = 0}^\infty \{X_0 \not\in A, X_1 \not\in A, \dots, X_{n - 1} \not\in A, X_n \in A\} \] \begin{align*} \PP_i(\tau_A < \infty) &= \sum_{n = 1}^\infty \PP_i(X_1 \not\in A, \dots, X_{n - 1} \not\in A, X_n \in A) \\ &= \PP_i(X_1 \in A) + \sum_{n = 2}^\infty \PP_i(X_1 \not\in A, \dots, X_{n - 1} \not\in A, X_n \in A) \end{align*} Now compute: \begin{align*} \PP_i(X_1 \not\in A, \dots, X_{n - 1} \not\in A, X_n \in A) &= \sum_{j \not\in A} \PP_i(X_1 = j, X_2 \not\in A, \dots, X_{n - 1} \not\in A, X_n \in A) \\ &= \sum_{j \not\in A} \PP_i(X_2 \not\in A, \dots,X_{n - 1} \not\in A, X_n \in A \mid X_0 = i, X_1 = j) P(i, j) \\ &= \sum_{j \not\in A} P(i, j) \PP_j(X_1 \not\in A, \dots, X_{n - 2} \not\in A, X_{n - 1} \in A) \end{align*} Now plus back in: \begin{align*} h_i^A &= \PP_i(X_1 \in A) + \sum_{n = 1}^\infty \sum_{j \not\in A} P(i, j) \ub{\PP_j(X_1 \not\in A, \dots, X_n \in A)}_{h_j^A} \\ &= \sum_{j \in A} P(i, j) \ub{h_j^A}_{=1} + \sum_{j \not\in A} P(i, j) h_j^A \\ \implies h_i^A &= \sum_j P(i, j) h_j^A \end{align*} So $h_i^A$ is a solution as claimed. \myskip Now we prove minimality. Let $(x_i)$ be another non-negative solution. Need to show that $h_i^A \le x_i$ for all $i$. If $i \not\in A$, then \[ x_i = \sum_j P(i, j) x_j \] \[ \implies x_i = \sum_{j \in A} P(i, j) + \sum_{j \not\in A} P(i, j) x_j \] \begin{align*} x_i &= \sum_{j \in A} P(i, j) + \sum_{j \not\in A} \sum_{j \in A} P(i, j)P(j, k) + \sum_{j \not\in A} \sum_{k \not\in A} P(i, j)P(j, k) x_k \\ x_i &= \PP_i(X_1 \in A) + \PP_i(X_1 \not\in A, X_2 \in A) + \sum_{j \not\in A} \sum_{k \not\in A} P(i, j)P(j, k) x_k \\ x_i &\ge \PP_i(X_1 \in A) + \PP_u(X_1 \not\in A, X_2 \not\in A) + \cdots + \PP_i(X_1 \not\in A, \dots, X_{n - 1} \not\in A, X_n \in A) \end{align*} (the inequality holds because the remaining terms are all non-negative since we assume that the $x_i$ are non-negative). Rewriting: \[ x_i \ge \PP_i(\tau_A \le n) \quad \forall n \in \NN .\] \[ \{\tau_A \le n\} \nearrow \bigcup_n \{\tau_A \le n\} = \{\tau_A < \infty\} \] so $\PP_i(\tau_A \le n) \nearrow \PP_i(\tau_A < \infty)$ hence $x_i \ge \PP_i(\tau_A < \infty) = h_i^A$. \end{proof}